Data Logging Sensor Kelembaban Tanah Menggunakan LabVIEW Pada Penyiram Tanaman Otomatis Dengan Kendali Arduino - Arif Ainur Rafiq (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
time. Besides that, watering plants manually requires a lot of energy. When the plantation area is wide, the owner can not use the time effectively. To overcome this problem, this tool is designed to help the user by using automatic watering method. The automatic watering sprayer uses a 3-way mechanical system of movement. Arduino Mega 2560 to control stepper motor and Arduino Uno for communication between hardware and LabVIEW. The data obtained will be visualized in percentage of moisture and also stored in data logging with excel format. Soil moisture sensor YL-69 is used for measuring the moisture on the soil. Measurements made in different plant area. The watering process is limited by the value of humidity, and LabVIEW will display the results in data logging.